Time - Jennings, Terry (Delhi. Bombay. Calcutta. Oxford university press., 1990)
Presents experiments and activities relating to the measurement of time, such as making a sundial, water clock, and candle clock.
Includes index.
Keywords: Time measurements -- Experiments -- Juvenile literature